Where do you draw the line? : functional flexibility, training & skill in Britain & France - O'Reilly, Jacqueline [Verfasser] (My University, 1992)
"This article argues that the concept of functional flexibility fails to make a clear distinction between a deliberate strategy to enhance skills and training, in contrast to where task enlargement has developed in an ad hoc manner, as a result of restructuring. By drawing on detailed research conducted in the retail banking sector in Britain and France it is argued that the flexibility debates need to be more clearly situated in the specific social and economic context of a given society." (author's abstract) ((en)) Der Beitrag geht der Frage nach, wie sich die Flexibilisierung von Banktätigkeiten in Grossbritannien und Frankreich ausgewirkt hat. Dabei werden die verschiedenen Konzepte der Personalbeschaffung und Mitarbeiterqualifizierung sowie das Tätigkeitsspektrum der Bankangestellten verglichen. (IAB)
Wo soll man die Trennlinie ziehen? - Funktionale Flexibilität, Ausbildung und Qualifikation in Grossbritannien und Frankreich
Keywords: G 1.2.3.1 Potenziale; G 2.3.5 Wirtschaftsstrukturwandel; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.4.2.4 Kredit und Versicherung; Bankberuf; Qualifikation; Strukturwandel; Job enlargement; Tätigkeitsmerkmal; Teilzeitarbeit; Personalgewinnung; Bankgewerbe; Berufsausbildung; Berufsproblem; Quantitative Angaben